Analyzing the relationship between corporate social responsibility and foreign direct investment - Ojo, Marianne (Hershey, PA : Business Science Reference, An Imprint of IGI Global, 2016)
'This book explores the relationship between ethical and environmental standards and foreign investment on the international market, investigating the benefits of practicing CSR as a means of sustainable economic growth and to mitigate devastating negative consequences, especially in the developing world'--
Includes bibliographical references (pages 283-315) and index.
Keywords: Social responsibility of business; Investments, Foreign; Investments, Foreign -- Developing countries; Banks and banking